Motivational Factors in Physiotherapy Games - LIND, JONATAN; MIKKO, ANDREAS (My University, 2017)
Physiotherapy can be a long process. Exercises can be mundane and the progress slow. For the patient, it can thus be difficult to maintain the motivation needed to follow through with the physiotherapy. Especially at home where the physiotherapist is not available to provide help. Games’ ability to engage the user could potentially be used to help the patient to stay motivated. It is not obvious how one should design physiotherapy games to make them motivating to play. Hence, this thesis asks what factors should be considered, to maintain user motivation, when designing a physiotherapy game. To find the factors, several subjects areas were explored, including interaction design, game design, gamification, motivation theory and physiotherapy. Theoretical knowledge was gathered by consulting previous studies, existing commercial games and through interviews with experts within the healthcare and rehabilitation field. The theoretical knowledge was then put into practice. By going through a design process, a concept and a prototype for a physiotherapy game was developed. The game was named Kinetispace - a game that uses Kinect to detect when the player performs physiotherapy exercises to refuel a spaceship. Kinetispace was playtested with school children to evaluate the prototype. In total, 22 different factors, to consider regarding motivation in physiotherapy games, were identified. These factors were then divided into eight categories. The list of factors is not definitive as more factors may exist. Also, no conclusions regarding the factors impact on long term motivation can be drawn since the factors should be considered as preliminary results for further studies. They can also serve as a vocabulary for discussing motivation when designing games.
Keywords: Informations- och kommunikationsteknik; Data- och informationsvetenskap; Information & Communication Technology; Computer and Information Science